Deferred stent implantation in patients with ST segment elevation myocardial infarction with high thrombus burden - Mohamed Abdel-shafy Tabl; Khaled Emad El-Rabbat; Eman Said El-keshk; Gamal Mohamed Gharib (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2019)
Recent guidelines recommend against deferred stenting as a routine strategy in STEMI patients.  Objectives: current study aimed to assess whether deferred stenting strategy in primary PCI might reduce angiographic or in-hospital major adverse cardiac events in comparison to immediate stenting.  Methods: one hundred patients of STEMI with high thrombus burden divided equally into; 50 patients (group 1) treated with immediate stenting and 50 patients (group 2) treated with deferred stenting. Procedural angiographic events were the primary endpoints, while in hospital MACE were designed as secondary endpoints.  Results: patients of deferred stenting group had statistically significant reduction of distal embolization, slow flow and no reflow (P value = 0.016). In contrast, deferred strategy didn't improve the short term clinical outcomes. Composite of MACEs was statistically significant in the deferred stenting group (20%) versus only (6%) in the immediate stenting group (P value = 0.037).  Conclusion: Deferred stenting in patients with STEMI those with high thrombotic burden improves only the angiographic outcomes but could not improve the short term clinical outcomes in comparison to immediate stenting. Deferred stenting shouldn't be used as a routine strategy in STEMI patients.